A Styrene-alt-Maleic Acid Copolymer Is an Effective Inhibitor of R5 and X4 Human Immunodeficiency Virus Type 1 Infection. (22nd April 2010) - Pirrone, Vanessa; Passic, Shendra; Wigdahl, Brian; Rando, Robert F.; Labib, Mohamed; Krebs, Fred C.
Abstract : An alternating copolymer of styrene and maleic acid ( alt -PSMA) differs from other polyanionic antiviral agents in that the negative charges of alt -PSMA are provided by carboxylic acid groups instead of sulfate or sulfonate moieties. We hypothesized that alt -PSMA would have activity against human immunodeficiency virus type 1 (HIV-1) comparable to other polyanions, such as the related compound, poly(sodium 4-styrene sulfonate) (PSS). In assays using cell lines and primary immune cells, alt -PSMA was characterized by low cytotoxicity and effective inhibition of infection by HIV-1 BaL and IIIB as well as clinical isolates of subtypes A, B, and C. In mechanism of action assays, in which each compound was added to cells and subsequently removed prior to HIV-1 infection ("washout" assay), alt -PSMA caused no enhancement of infection, while PSS washout increased infection 70% above control levels. These studies demonstrate that alt -PSMA is an effective HIV-1 inhibitor with properties that warrant further investigation.